So hard to say - Sanchez, Alex, 1957- (New York : Simon & Schuster Books for Young Readers, 2004)
Thirteen-year-old Xio, a Mexican American girl, and Frederick, who has just moved to California from Wisconsin, quickly become close friends, but when Xio starts thinking of Frederick as her boyfriend, he must confront his feelings of confusion and face the fear that he might be gay.
Accelerated Reader AR
Keywords: Homosexuality -- Fiction; Mexican Americans -- Fiction; Interpersonal relations -- Fiction; Schools -- Fiction; California -- Fiction